Cake or death? Ending confusions about asymmetries between consent and refusal. Issue 11 (16th September 2016) - Lawlor, Rob
Abstract : In this paper, I will argue that much of the debate concerning asymmetries between consent and refusal (eg, in a case in which an adolescent is granted a right to consent to treatment, but not a right to refuse treatment) is confused. My aim in this paper is to highlight nuances and ambiguities, and to emphasise the fact that we are not just addressing a puzzle about one asymmetry between consent and refusal. I will show that there are a number of relevant asymmetries, not just the asymmetry of competence. And even if we focus specifically on the asymmetry of competence, we need to recognise that 'asymmetry of competence' is ambiguous. By clarifying these issues, my aim is to end the confusion that is common in this debate, allowing us to make progress on an issue that has previously been considered puzzling.